Respostas
respondido por:
1
Achando a raiz do divisor:
\begin{gathered}2x-3=0\\2x=3\\\\\=\dfrac{3}{2}}}\end{gathered}2x−3=02x=3x=23
Achando o resto da divisão:
\begin{gathered}R(x)=P(\frac{3}{2})\\\\R(x)=2(\frac{3}{2})^{3}-5(\frac{3}{2})^{2}+4(\frac{3}{2})-4\\\\R(x)=2(\frac{27}{8})-5(\frac{9}{4})+2(3)-4\\\\R(x)=\frac{54}{8}-\frac{45}{4}+2\\\\R(x)=\frac{54}{8}-\frac{90}{8}+\frac{16}{8}\\\\R(x)=\frac{54-90+16}{8}\\\\R(x)=-\frac{20}{8}\\\\\\\boxed{\boxed{R(x)=-\frac{5}{2}}}\end{gathered}R(x)=P(23)R(x)=2(23)3−5(23)2+4(23)−4R(x)=2(827)−5(49)+2(3)−4R(x)=854−445+2R(x)=854−890+816R(x)=854−90+16R(x)=−820R(x)=−25
cameloqdoi:
oq seria essas frases no meio da conta
Perguntas similares
3 anos atrás
3 anos atrás
3 anos atrás
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás